Inventory Parameters - Sharma, Sanjay; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
This book provides a detailed overview of various parameters/factors involved in inventory analysis. It especially focuses on the assessment and modeling of basic inventory parameters, namely demand, procurement cost, cycle time, ordering cost, inventory carrying cost, inventory stock, stock out level, and stock out cost. In the context of economic lot size, it provides equations related to the optimum values. It also discusses why the optimum lot size and optimum total relevant cost are considered to be key decision variables, and uses numerous examples to explain each of these inventory parameters separately. Lastly, it provides detailed information on parameter estimation for different sectors/products. Written in a simple and lucid style, it offers a valuable resource for a broad readership, especially Master of Business Administration (MBA) students.
Introduction -- Demand -- Ordering cost -- Inventory carrying cost -- Procurement cost -- Cycle time -- Stock out.
Keywords: Industrial engineering; Production engineering; Business logistics; Strategic planning; Leadership; Industrial and Production Engineering; Supply Chain Management; Business Strategy and Leadership